Mortality and complications following visceral surgery: a nationwide analysis based on the diagnostic categories used in German hospital invoicing data - Baum, Philip; Diers, Johannes; Lichthardt, Sven; Kastner, Carolin; Schlegel, Nicolas; Germer, Christoph-Thomas; Wiegering, Armin (Deutsches Ärzteblatt, 2019)
Surgery represents a fundamental pillar of treatment for a multitude of diseases. In the case of life-threatening indications such as appendicitis (1) or cancer therapy (e.g., treatment of colorectal liver metastases [2]), a surgical approach is...
Gesehen am 16.02.2022